Dominance of recombinant DWV genomes with changing viral landscapes as revealed in national US honey bee and varroa mite survey - Poppy J. Hesketh-Best; Dean A. Mckeown; Krisztina Christmon; Steven Cook; Anne Marie Fauvel; Nathalie A. Steinhauer; Declan C. Schroeder (Communications Biology)
Abstract Honey bees are essential pollinators for global agriculture. The viromes of US commercial apiaries and their ectoparasitic mites are poorly characterized at a strain level and there is a need to integrate genomics into pathogen surveillance. We sequenced RNA viromes from 383 adult bees and 173 mites pooled samples from 11 major US beekeeping hubs in 2021, assembling 45 complete and 1702 partial genomes. Protein sequence similarity networks and recombinant genome identification revealed a new viral landscape. Sinaivirus (n = 312), Iflavirus sacbroodi (n = 280), and Iflavirus aladeformis (DWV, n = 135) genomes were common. Recombinant DWV genomes with high nucleotide identity were widespread, and DWV type A master variants were rare, with an indication that RT-PCR surveillance may over-detect type A due to the prevalence of recombinant DWV genomes. Future work should use genomic strategies to avoid misidentification of common honey bee virus genomes and their impact on colony health.